Tumor cell plasticity, heterogeneity, and resistance in crucial microenvironmental niches in glioma - Erik Jung (Nature Portfolio, 2021)
Whether the perivascular niche (PVN) and the integration into multicellular networks by tumor microtubes (TMs) have a different role in glioblastoma progression and resistance to therapies is currently unclear. Here, the authors, by long-term tracking of individual glioma, demonstrate that both niches can partially compensate for each other and that glioma cells localized in both niches are resistant to radio- and chemotherapy.